Risperidona diminui a resposta ap estresse em peixe-zebra (Danio rerio) - Idalencio, Renan (2015)
Contamination of water resources be they municipal wastewater or surface water, by drugs and their metabolites have been reported since the 70s, endangering the user population of these resources as well as the aquatic habitat. Risperidone, an atypical antipsychotic used to treat patients with schizophrenia, psychosis, Alzheimer's disease and autism found in wastewater in environmental concentration 0,00034μg/L. This drug possesses anxiolytic and antidepressant power but to the development of this experiment are not sure if it could be somehow interfering with the neuroendocrine system of fish stress. The activation of the hypothalamic-pituitary-interrenal axis (HPI) and consequent elevation of cortisol in fish occur when exposed to an attacker, be it predator, reduced oxygen or contamination by drugs. In zebrafish the stress response has similarity to those of terrestrial vertebrates in that it involves consumption and oxygen transfer, energy mobilization, growth, reproduction and effects on immune functions. The zebrafish was used because of its rapid growth and ease of maintenance, as well as its homology with humans, more studies with toxicology, pharmacology and behavior. This study was conducted at the Fish Physiology Laboratory, Faculty of Agronomy and Veterinary Medicine (FAMV), University of Passo Fundo (UPF), first evaluated front cortisol levels to five different concentrations (0,00034, 8, 170, 340 and 680μg/L) and risperidone on four different times (-15, 15, 60 and 240'), with acute drug exposure(15'). As result is found is that risperidone in the presence of water interferes with the HPI axis at a concentration of 170μg/L in time 15 minutes after stress, continuing then to the second part of the experiment where the zebrafish behavior was evaluated in concentration effect. The observed parameters were the distance traveled, average speed,the absolute angle turn, the number of intersections between the lower compartments, secondary and higher and the length of stay in the lower compartments, secondary and higher. In animal behavior test remained along the bottom of comparing the stress with the stress more risperidone , can be considered , risperidone, an anxiolytic .